The Relationship Of Pregnant Women's Knowledge And Attitude To The Implementation Of Delivery Planning And Complication Prevention (P4k) Program - Ratih Ruhayati (Rifa'Institute, 2021)
Maternal Mortality Rate (MMR) and Infant Mortality Rate (IMR) are indicators to assess the health status of the community. Based on the Indonesian Demographic and Health Survey 2017 IDHS, the maternal mortality rate in Indonesia is still high at 302 per 100,000 live births, while the infant mortality rate is 24 per 1000 live births. The decline in MMR and IMR cannot be separated from the role of community empowerment, one of which is carried out through the implementation of the Childbirth Planning and Complications Prevention Program (P4K). Most mothers, husbands, and families have less active role in the implementation of P4K, even though there is an effect of implementing P4K on neonatal mortality. This happens because the mother's knowledge about P4K is still lacking, so her attitude is still not positive. The purpose of this study was to determine the relationship between knowledge and attitudes of pregnant women towards the implementation of the Childbirth Planning and Complications Prevention (P4K) Program. The research design used